Octominin: An antimicrobial peptide with antibacterial and anti-inflammatory activity against carbapenem-resistant Escherichia coli both in vitro and in vivo - Jingchun Kong; Yue Wang; Yijia Han; Huijing Zhou; Zhenyun Huang; Xiaodong Zhang; Cui Zhou; Jianming Cao; Tieli Zhou (Journal of Global Antimicrobial Resistance, 2023)
ABSTRACT: Objectives: The emergence of carbapenem-resistant Escherichia coli (CREC) is a global concern as its prevalence restricts treatment options and poses a considerable threat to public health. In this study, in vitro and in vivo activity of the antimicrobial peptide Octominin against CREC was investigated to reveal possible mechanisms of action. Furthermore, its safety and factors influencing its antibacterial effect were assessed. Additionally, the anti-inflammatory effects of Octominin were examined. Methods: The antimicrobial activity of Octominin against 11 strains of CREC was determined using the broth microdilution method, growth curve, and time-kill assay. Its possible mechanism of action was unraveled using the propidium iodide and N-phenyl-1-naphthylamine fluorochrome and lipopolysaccharide-binding assays. To understand the safety and stability of Octominin, its cytotoxicity, hemolysis, and antibacterial activity under various conditions (i.e, temperature, ions) were estimated. Additionally, a Galleria mellonella infection model was utilized to evaluate the efficacy of Octominin in vivo, and qRT-PCR was performed to assess its effect on the expression of proinflammatory cytokines. Results: Octominin displayed a significant antibacterial effect, with MICs of 4–8 µg/mL and MBCs of 8–16 µg/mL. Octominin exerted its antibacterial effect by disrupting bacterial membranes. Cytotoxicity and hemolysis tests demonstrated the potential application of Octominin in vivo. The G. mellonella infection model asserted the in vivo efficacy of Octominin. Furthermore, Octominin inhibited the expression of proinflammatory cytokines. Although the temperature had little effect on its the activity, serum and ions reduced activity. Conclusion: Octominin is a promising alternative agent with remarkable antibacterial and anti-inflammatory effects for treating infections caused by CREC.